Genetic diversity and verification of plant material compliance of Cocoa (Theobroma cacao L.) in the Barombi-Kang Regional variety trial - Nto Marie Claire Eyango; Olivier Sounigo; Olivier Fouet; Honoré Tekeu; François Pierre Djocgoué; Mousseni Ives Bruno Efombagn; Claire Lanaud (PLoS ONE, 2025)
Cocoa (Theobroma cacao L.) is a pivotal agricultural commodity in Cameroon, which ranks as one of the top five global cocoa producers. This study focused on evaluating the genetic diversity and verifying the plant material compliance of cocoa genotypes in the Barombi-Kang Regional variety trial, employing 12 highly polymorphic SSR markers. A comprehensive analysis of 318 hybrid families and 15 parental genotypes was conducted, which revealed extensive genetic variability. The study found an average polymorphic information content (PIC) of 0.72 for hybrids and 0.68 for parents, alongside observed heterozygosity rates of 0.54 and 0.42, respectively, indicating a rich genetic reservoir. Significantly, an 18.55% labeling error rate was identified, underscoring prevalent issues in germplasm management that could impact the efficacy of breeding programs. These errors highlight the critical need for enhanced genetic verification protocols to ensure the accuracy and reliability of plant materials used in breeding. The genetic analysis also demonstrated substantial allelic richness with the hybrids showing an average of 72 alleles per locus, suggesting a high capacity for selection within the breeding pool. The data from this study not only reinforce the potential for genetic improvement of cocoa in Cameroon but also provide crucial insights into the genetic structure and population dynamics within the trial. Addressing the genetic and management challenges identified could lead to the development of superior cocoa varieties, enhancing yield, disease resistance, and environmental stress tolerance, thereby contributing to the sustainable advancement of the cocoa industry in Cameroon and beyond.